2017
DOI: 10.1128/jvi.02503-16
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Human Coronavirus NL63 N Protein

Abstract: Coronaviruses are responsible for upper and lower respiratory tract infections in humans. It is estimated that 1 to 10% of the population suffers annually from cold-like symptoms related to infection with human coronavirus NL63 (HCoV-NL63), an alphacoronavirus. The nucleocapsid (N) protein, the major structural component of the capsid, facilitates RNA packing, links the capsid to the envelope, and is also involved in multiple other processes, including viral replication and evasion of the immune system. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 55 publications
(58 reference statements)
4
41
0
Order By: Relevance
“…Self-association of the fulllength SARS-CoV N protein and the isolated C-terminal region (domains N2b plus spacer B/N3; residues 210-422) was first demonstrated by yeast two-hybrid analysis 31 , and the purified fulllength protein was shown to self-associate into predominantly dimers in solution 32 . The structures of the N2b domain of SARS-CoV and several related coronaviruses confirmed the obligate homodimeric structure of this domain [33][34][35][36][37][38][39] , and other work showed that the region Cterminal to this domain mediates further self-association into tetramer, hexamer, and potentially higher oligomeric forms [40][41][42] . Other studies have suggested that the protein's Nterminal region, including the RNA-binding N1b domain, can also self-associate 43,44 , highlighting the possibility that assembly of full-length N into helical filaments is mediated by cooperative interactions among several interfaces.…”
Section: Structure Of the Sars-cov-2 Nucleocapsid Dimerization Domainsupporting
confidence: 53%
See 2 more Smart Citations
“…Self-association of the fulllength SARS-CoV N protein and the isolated C-terminal region (domains N2b plus spacer B/N3; residues 210-422) was first demonstrated by yeast two-hybrid analysis 31 , and the purified fulllength protein was shown to self-associate into predominantly dimers in solution 32 . The structures of the N2b domain of SARS-CoV and several related coronaviruses confirmed the obligate homodimeric structure of this domain [33][34][35][36][37][38][39] , and other work showed that the region Cterminal to this domain mediates further self-association into tetramer, hexamer, and potentially higher oligomeric forms [40][41][42] . Other studies have suggested that the protein's Nterminal region, including the RNA-binding N1b domain, can also self-associate 43,44 , highlighting the possibility that assembly of full-length N into helical filaments is mediated by cooperative interactions among several interfaces.…”
Section: Structure Of the Sars-cov-2 Nucleocapsid Dimerization Domainsupporting
confidence: 53%
“…The structure of N 2b closely resembles that of related coronaviruses, including SARS-CoV, Infectious Bronchitis Virus (IBV), MERS-CoV, and HCoV-NL63 [33][34][35][36][37][38] . The structure is particularly similar to that of SARS-CoV, with which the N2b domain shares 96% sequence identity; only five residues differ between these proteins' N2b domains (SARS-CoV Gln268  SARS-CoV-2 A267, D291E290, H335Thr334, Gln346Asn345, and Asn350Gln349), and the structures are correspondingly similar with an overall Cα r.m.s.d of 0.44 Å across the N 2b dimer (Figure 1C).…”
Section: Structure Of the Sars-cov-2 Nucleocapsid Dimerization Domainmentioning
confidence: 82%
See 1 more Smart Citation
“…HCoV-NL63 is primarily infected children and those immunocompromised with either moderate upper respiratory symptoms such as cough, fever, and rhinorrhoea or severe LRTI, such as bronchiolitis and croup, perceived primarily in younger children (Abdul-Rasool and Fielding, 2010). It is estimated that 1-10% of the population is affected annually by cold-like symptoms of HCoV-NL63 (Szelazek et al, 2017) .…”
Section: Human Coronavirus Typesmentioning
confidence: 99%
“…The N-terminus of the N protein (residues 39-165) may be the RNA-binding region, and the C-terminus may be a self-binding oligomer-forming region [28]. A comparison of homology between MERS-CoV and other CoVs shows that although the N protein has low homology over the entire amino acid sequence, certain local amino acid sequences-especially the N-terminal amino acid sequence-are highly conserved.…”
Section: Virion Replication and Assemblymentioning
confidence: 99%